The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.2478/acmy-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Potentially Toxic Elements from Poultry Feeds in Ebonyi State, Nigeria

Abstract: This study examined potentially toxic elements (PTEs) from poultry feeds. The presence of PTEs in the environment raises health concern because these elements can be toxic, ubiquitous and cannot be degraded to non-toxic forms by any known method and as a result remain in the environment for decades. This is a potential pathway through which these PTEs could easily enter the food chain. Six PTEs (Cd, Cr, Cu, Pb, Mn, Ni and Zn) were determined from four feed types (starter, grower, finisher and layer) from four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(15 reference statements)
0
2
1
Order By: Relevance
“…The observed values were lower than the values of 2.250 -4.875 mg/kg obtained by [12]. Comparing with the studies conducted by [21] indicated that all samples were above the maximum acceptable limit.…”
Section: Nickelcontrasting
confidence: 65%
See 1 more Smart Citation
“…The observed values were lower than the values of 2.250 -4.875 mg/kg obtained by [12]. Comparing with the studies conducted by [21] indicated that all samples were above the maximum acceptable limit.…”
Section: Nickelcontrasting
confidence: 65%
“…According to [21], nickel influences Fe absorption and metabolism, and may be an essential component of the haemopoietic process in humans. However, when in excess, it can cause respiratory disease [16].…”
Section: Nickelmentioning
confidence: 99%
“…Based on the study by Eloma et al [56], which analyzed six potentially toxic elements (PTEs) from poultry feeds such as Cd, Cr, Cu, Pb, Mn, Ni and Zn, four feed forms (starter, grower, finisher and layer) from four producers coded A, B, C and D were sold in Ebony State, Nigeria. The mean concentrations of metals recorded from poultry feeds were as following: Chromium (11.9-7.90 mg/kg); Copper (5.10-7.91 mg/kg); Cadmium (0.49-0.76 mg/kg); Lead (7.17-9.47 mg/kg); Manganese (26.9-34.9 mg/kg); Nickel (3.80-6.50 mg/kg) and Zinc (27.8-38.4 mg/kg).…”
Section: Recent Research On the Quality Of Heavy Metals In Poultry Feedmentioning
confidence: 99%